Pneumocystis Pneumonia Presenting as an Enlarging Solitary Pulmonary Nodule - Krunal Bharat Patel; James Benjamin Gleason; Maria Julia Diacovo; Nydia Martinez-Galvez (Case Reports in Infectious Diseases)
Pneumocystis pneumonia is a life threatening infection that usually presents with diffuse bilateral ground-glass infiltrates in immunocompromised patients. We report a case of a single nodular granulomatous Pneumocystis pneumonia in a male with diffuse large B-cell lymphoma after R-CHOP therapy. He presented with symptoms of productive cough, dyspnea, and right-sided pleuritic chest pain that failed to resolve despite treatment with multiple antibiotics. Chest X-ray revealed right lower lobe atelectasis and CT of chest showed development of 2 cm nodular opacity with ground-glass opacities. Patient underwent bronchoscopy and biopsy that revealed granulomatous inflammation in a background of organizing pneumonia pattern with negative cultures. Respiratory symptoms resolved but the solitary nodular opacity increased in size prompting a surgical wedge resection which revealed granulomatous Pneumocystis pneumonia infection. This case is the third documented report of Pneumocystis pneumonia infection within a solitary pulmonary nodule in an individual with hematologic neoplasm. Although Pneumocystis pneumonia most commonly occurs in patients with HIV/acquired immunodeficiency syndrome and with diffuse infiltrates, the diagnosis should not be overlooked when only a solitary nodule is present.